2022
DOI: 10.3390/toxics10060313
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Risk Assessment of Pesticides through the Integration of Human Biomonitoring and Food Monitoring Data: A Case Study for Chlorpyrifos

Abstract: The risk assessment of pesticide residues in food is a key priority in the area of food safety. Most jurisdictions have implemented pre-marketing authorization processes, which are supported by prospective risk assessments. These prospective assessments estimate the expected residue levels in food combining results from residue trials, resembling the pesticide use patterns, with food consumption patterns, according to internationally agreed procedures. In addition, jurisdictions such as the European Union (EU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…While the common metabolites associated with the 3-phenoxybenzyl alcohol moiety facilitate screening assessments [ 19 ], the lack of unique urinary metabolites adds complexity for refining the risk, triggering our previous proposal for a tiered approach [ 9 ]. As dietary exposure is the most significant for the general population, the EU-wide information on pesticide residues in food annually reported by EFSA has been proposed by several authors as an information source for risk refinement [ 16 , 20 ]. The comprehensive European food consumption database [ 21 ] has not been implemented for pesticide risk assessment yet; the EFSA Model PRIMo [ 15 ] is based on national diets provided by EU member states; the overall representativeness of each diet for the European citizens has been questioned [ 20 ] and the worst-case was selected for proposing regulatory options.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the common metabolites associated with the 3-phenoxybenzyl alcohol moiety facilitate screening assessments [ 19 ], the lack of unique urinary metabolites adds complexity for refining the risk, triggering our previous proposal for a tiered approach [ 9 ]. As dietary exposure is the most significant for the general population, the EU-wide information on pesticide residues in food annually reported by EFSA has been proposed by several authors as an information source for risk refinement [ 16 , 20 ]. The comprehensive European food consumption database [ 21 ] has not been implemented for pesticide risk assessment yet; the EFSA Model PRIMo [ 15 ] is based on national diets provided by EU member states; the overall representativeness of each diet for the European citizens has been questioned [ 20 ] and the worst-case was selected for proposing regulatory options.…”
Section: Discussionmentioning
confidence: 99%
“…The EFSA annual reports on food monitoring data have been previously used for comparing dietary estimations with real human biomonitoring data for pesticides such as chlorpyrifos with simple metabolic profiles [ 16 ]. Our results confirm their potential use for informing more complex situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study, based on food monitoring and human biomonitoring, showed strong reductions of CHLP usage from 2016 onwards, which can be ascribed to regulations and awareness of the potentially harmful effects of CHLP [ 23 ]. In addition, the production of CHLP by Dow Chemical/Coverta was halted [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When no HBM data are available, for example, in the case of prospective assessments, the internal dose of a pesticide in human can be estimated by the expected residue levels in food. Tarrazona et al (2022) [ 13 ] compared consumers’ internal exposure to chlorpyrifos based on the urinary marker 3,5,6-trichloro-2-pyridinol (TCPy), using two sources of monitoring data: monitoring of the food chain from the EU program and biomonitoring of European citizens from the HBM4EU initiative, supported by a literature search. Both methods confirmed a drastic reduction in the exposure levels from 2016 onwards.…”
mentioning
confidence: 99%